Guiding therapeutic plasma exchange for antibody‐mediated rejection treatment in lung transplant recipients – a retrospective study. (26th February 2021) - Timofeeva, Olga A.; Choe, Jason; Alsammak, Mohamed; Yoon, Edward J.; Geier, Steven S.; Mathew, Leena; McCollick, Amanda; Carney, Kevin; Au, Jenny; Diamond, Adam; Galli, Jonathan A.; Shenoy, Kartik; et al.
Summary: Antibody‐Mediated Rejection (AMR) due to donor‐specific antibodies (DSA) is associated with poor outcomes after lung transplantation. Currently, there are no guidelines regarding the selection of treatment protocols. We studied how DSA characteristics including titers, C1q, and mean fluorescence intensity (MFI) values in undiluted and diluted sera may predict a response to therapeutic plasma exchange (TPE) and inform patient prognosis after treatment. Among 357 patients consecutively transplanted without detectable pre‐existing DSAs between 01/01/16 and 12/31/18, 10 patients were treated with a standardized protocol of five TPE sessions with IVIG. Based on DSA characteristics after treatment, all patients were divided into three groups as responders, partial responders, and nonresponders. Kaplan–Meier Survival analyses showed a statistically significant difference in patient survival between those groups ( P = 0.0104). Statistical analyses showed that MFI in pre‐TPE 1:16 diluted sera was predictive of a response to standardized protocol ( R 2 = 0.9182) and patient survival ( P = 0.0098). Patients predicted to be nonresponders who underwent treatment with a more aggressive protocol of eight TPE sessions with IVIG and bortezomib showed improvements in treatment response ( P = 0.0074) and patient survival ( P = 0.0253). Dilutions may guide clinicians as to which patients would be expected to respond to a standards protocol or require more aggressive treatment.